COMPARATIVE EFFECT OF “AS LUPINUS” AND GLYCORAZMULIN ON THE HIGH-CONDUCTANCE PORE OF RAT LIVER MITOCHONDRIA UNDER ALLOXAN-INDUCED DIABETES CONDITIONS (Scientific journal of the Fergana State University, 2026)
This study investigated the antioxidant activity of a mixture of Japanese (Sophora japonica L), which grows in Uzbekistan, and lupin (Lupinus angustifolius L). It was found that a 1:1 ratio of the mixture exhibits high antioxidant activity. Based on this 1:1 mixture, a biologically active food supplement for the treatment of diabetes was developed, named “As Lupinus.” To analyze the biological activity of the “As Lupinus” supplement under alloxan-induced diabetic conditions, a comparative study of its effects and those of glycorasmulin on the high-permeability pore of rat liver mitochondria was conducted in vivo at the Tashkent Institute of Bioorganic Chemistry. The aim of the study is to conduct preclinical investigations of the biological activity of the “As Lupinus” supplement and to develop antidiabetic food supplements for diabetes treatment and their practical application.